![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) x4 + 6x3 + 11x2 + 6x + 1 = 0 <=> ( x2 + 3x + 1 ) 2 = 0 <=> x2 + 3x + 1 = 0
|
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{3x}{x-2}-\frac{x}{x-5}+\frac{9x}{x^2-7x+10}=10\)
\(\Rightarrow\frac{3x^2-15x-x^2+2x+9x}{x^2-7x+10}=10\)
\(\Rightarrow\frac{2x^2-4x}{x^2-7x+10}=10\)
\(\Rightarrow2x^2-4x=10x^2-70x+100\)
\(\Rightarrow8x^2-66x+100=0\)
Ta có \(\Delta=66^2-4.8.100=1156,\sqrt{\Delta}=34\)
\(\Rightarrow\orbr{\begin{cases}x=\frac{66+34}{16}=\frac{25}{4}\\x=\frac{66-34}{16}=2\end{cases}}\)
a) \(\frac{3x}{x-2}-\frac{x}{x-5}+\frac{9x}{x^2-7x+10}=10\)
<=> \(\frac{3x\left(x-5\right)}{\left(x-2\right)\left(x-5\right)}-\frac{x\left(x-2\right)}{\left(x-5\right)\left(x-2\right)}+\frac{9x}{\left(x-2\right)\left(x-5\right)}=10\)
<=> \(\frac{3x^2-15x-x^2+2x+9x}{\left(x-5\right)\left(x-2\right)}=10\)
<=> \(\frac{2x^2-4x}{\left(x-5\right)\left(x-2\right)}=10\)
<=> \(\frac{2x\left(x-2\right)}{\left(x-5\right)\left(x-2\right)}=10\)
<=> \(2x=10\left(x-5\right)\)
<=> 2x - 10x = -50
<=> -8x = -50
<=>x = 6,25
Vậy S = {6,25}
b) (x - 7)(x - 2)(x - 4)(x - 5) = 72
<=> (x2 - 9x + 14)(x2 - 9x + 20) = 72
Đặt x2 - 9x + 14 = t <=> t(t + 6) = 72
<=> t2 + 6t - 72 = 0
<=> t2 + 12t - 6t - 72 = 0
<=> (t + 12)(t - 6) = 0
<=> \(\orbr{\begin{cases}t+12=0\\t-6=0\end{cases}}\)
<=> \(\orbr{\begin{cases}x^2-9x+14+12=0\\x^2-9x+14-6=0\end{cases}}\)
<=> \(\orbr{\begin{cases}\left(x-9x+20,25\right)+5,75=0\\x^2-9x+8=0\end{cases}}\)
<=> \(\orbr{\begin{cases}\left(x-4,5\right)^2+5,75=0\left(vn\right)\\x^2-x-8x+8=0\end{cases}}\)
<=> (x - 1)(x - 8) = 0
<=> \(\orbr{\begin{cases}x-1=0\\x-8=0\end{cases}}\)
<=> \(\orbr{\begin{cases}x=1\\x=8\end{cases}}\)
Vậy S = {1; 8}
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(x+3\right)^2-\left(4-x\right)\left(4+x\right)=10\)
<=> \(x^2+6x+9-\left(16-x^2\right)=10\)
<=> \(2x^2+6x-17=0\)
<=> \(x^2+3x-\frac{17}{2}=0\)
<=> \(\left(x+\frac{3}{2}\right)^2-\frac{43}{4}=0\)
<=> \(\left(x+\frac{3}{2}+\frac{\sqrt{43}}{2}\right)\left(x+\frac{3}{2}-\frac{\sqrt{43}}{2}\right)=0\)
<=> \(\orbr{\begin{cases}x+\frac{3}{2}+\frac{\sqrt{43}}{2}=0\\x+\frac{3}{2}-\frac{\sqrt{43}}{2}=0\end{cases}}\)
<=> \(\orbr{\begin{cases}x=\frac{-3-\sqrt{43}}{2}\\x=\frac{\sqrt{43}-3}{2}\end{cases}}\)
Vậy...
\((x+3)^2-(4-x)(4+x)=10\)
\(\Rightarrow x^2+6x+9-(16+4x-4x+x^2)=10\)
\(\Rightarrow x^2+6x+9-16-x^2=10\)
\(\Rightarrow6x+9=26\)
\(\Rightarrow6x=17\)
\(\Rightarrow x\in\varnothing\)
Ta có x(x - 10) + x(2- x) = -40
=>x2- 10x + 2x - x2 = -40
=> -8x = -40
=> x = 5
Vậy x = 5
\(x\left(x-10\right)+x\left(2-x\right)=40\)
\(x^2-10x+2x-x^2=40\)
\(-8x=40\)
\(x=-5\)